GIS-TEHNOLOGI EXPOSURE OF LANDSLIDE PROCESSES OF SOILS: Array - , Л. М. (Municipal economy of cities. Series: «Economy science», 2018)
Landslides destroy the Earth surface, especially sharply this phenomenon takes place in settlements, where the landslides subject to dwelling building and in particular private houses. Destruction of soil cover - landslides conduce to destruction of dwelling-houses. The timely exposure of landslide processes of soil in settlements prevents further negative consequences. We investigated development of landslide in a village Ноvomlinsk Dvurihcanski district of the Kharkov area, where in latter days the landslide a whole street was exposed to - Garden, dwelling-houses collapsed. By our researches with the use of DZZ and space information the zones of mushroom growth of landslide were educed. After the exposure of landslide was done geodesic researches in the district of landslide, that confirmed space information about development of negative process. The use of GIS- technologies and DZZ allows in good time to react on the negative phenomena and warn their development. Space information allows to set the objects of degradation of soil cover. GIS- technologies is used at imposition on the raster of electronic digital map help to get the bitmapped image of locality with causing of the determined landed array on one of layers of digital information. From data of research in the програмном providing of Didgitals was built 3 - D model of зони action of landslide, that shows a zone and degree of further destruction of soil cover. Realization of monitoring of such earth with certain periodicity helps the use of modern GIS- technologies, ДЗЗ of space pictures and modern software. Monitoring of development of such phenomena is needed for the timely reacting, prognostication and warning of their development and acceptance of corresponding administrative decisions. Keywords: GIS- technologies, DZZ, changes of soil, degradation of the ground cover, destructive erosive processes, monitoring, systems of the surface basing, modern software, space pictures, informative layers, cadastre map.